FACTORS INFLUENCING INDONESIAN MILLENIALS’ TRAVEL DECISION: A CASE OF BANGKOK - Farida Komalasari; Eko Ganiarto (President University, 2020)
The number of Indonesian millenials visiting Bangkok is increase year by year. There must be a strong reason, why Indonesian millenials decide to visit Bangkok. This research aims to find out the factors influencing Indonesian millenials’ travel decision to visit Bangkok. The push and pull travel motivations theory are used to develop the research framework. A quantitative research with primary data collected by using a questionnaire is done. The data analysis used in this research is linear regression. There are two models, multiple linear regression and simple linear regression. A multiple linear regression is used to find out the factors of traveler satisfaction, while a simple linear regression is used to find out the influence of traveler satisfaction toward travel decision. The result shows that there are five push factors and five pull factors influencing traveler satisfaction, and at the end, traveler satisfaction influences travel decision. The five push factor are knowledge and culture, friendship, social status, sightseeing, and new experience. Meanwhile the five pull factors are local values, destinations features, historical values, cultural values, and outdoor attraction. Relaxation, as a part of push factor, does not influence traveler satisfaction.Keywords: Push and Pull Travel Motivations, Traveler Satisfaction, Travel Decision,Indonesian Millenial, Bangkok